From "Kidneys Govern Bones" to Chronic Kidney Disease, Diabetes Mellitus, and Metabolic Bone Disorder: A Crosstalk between Traditional Chinese Medicine and Modern Science. (7th September 2016) - Wang, Xiao-Qin; Zou, Xin-Rong; Zhang, Yuan Clare
Abstract : Although traditional Chinese medicine (TCM) and Western medicine have evolved on distinct philosophical foundations and reasoning methods, an increasing body of scientific data has begun to reveal commonalities. Emerging scientific evidence has confirmed the validity and identified the molecular mechanisms of many ancient TCM theories. One example is the concept of "Kidneys Govern Bones." Here we discuss the molecular mechanisms supporting this theory and its potential significance in treating complications of chronic kidney disease (CKD) and diabetes mellitus. Two signaling pathways essential for calcium-phosphate metabolism can mediate the effect of kidneys in bone homeostasis, one requiring renal production of bioactive vitamin D and the other involving an endocrine axis based on kidney-expressed Klotho and bone-secreted fibroblast growth factor 23. Disruption of either pathway can lead to calcium-phosphate imbalance and vascular calcification, accelerating metabolic bone disorder. Chinese herbal medicine is an adjunct therapy widely used for treating CKD and diabetes. Our results demonstrate the therapeutic effects and underlying mechanisms of a Chinese herbal formulation, Shen-An extracts, in diabetic nephropathy and renal osteodystrophy. We believe that the smart combination of Eastern and Western concepts holds great promise for inspiring new ideas and therapies for preventing and treating complications of CKD and diabetes.